Is environmental, social and governance (ESG) disclosure value enhancing? Evidence from top 100 companies / Raja Adzrin Raja Ahmad … [et al.] - Raja Ahmad, Raja Adzrin; Samsuddin, Mas Ervina; Azmi, Nurul Azlin; Abdullah, Norhidayah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Embracing environmental, social, and governance (ESG) megatrend among Malaysian firms is becoming crucial as ESG compliance and disclosure are still in the infancy stage, especially after the coronavirus disease (COVID-19) outbreak. Aligned with the government’s initiatives, this study examined the effects of ESG disclosure on firm performance. Using 180 firm-year observations from the top 100 firms listed on Bursa Malaysia from 2018 to 2021, we found that the ESG score boosted firm performance, as its disclosure attracted investor confidence and indirectly increased investment and firm performance. However, it was discovered that controversies provide a positive signal to investors in emerging countries as it improved their firm performance; further analysis was conducted to investigate which ESG pillars had a positive effect on the firm performance. The social pillar was associated with higher firm performance as it can influence workplace culture and indirectly increase firm performance. Contrasting findings were also found on the governance pillar on firm performance which indicated that governance did not improve firm performance directly, but good governance may contribute to better ESG investment and disclosure. Indirectly, it can improve firm performance. This study adds important evidence on the effects of ESG pillars and ESG controversies on firm performance.